Swear Words Used by Undergraduate Students of Engineering College in Surabaya - Rakhmaniyah Rakhmaniyah (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2013)
Swear words are kind of forbidden words that most of people think it does not allow occur in their conversation. However, some people try to break the rule; by using swear words in their daily conversations. It often occurs among undergraduate students, that is why the researcher find it interesting to identify the swear words choice that are used by undergraduate students of Engineering College in Surabaya as well as the type of swear word and their purposes. The researcher got the data through observation, recording and questionnaire. After collecting the data, the findings were analyzed by classifying, categorizing and describing the swear word that undergraduate students of Engineering used. The result of this research indicates that although many students came from outside Surabaya, the swear words which is more frequently they used is the term of sex such as “cuk” and “Jancuk”. Now swearing has become habitual in their social life, most of them use swear words just to express some humor or display closeness in friendship rather than to insult or to show their emotion.